2007
DOI: 10.1111/j.1550-7408.2007.00275.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oxidative and Nitrosative Stress on Tetrahymena pyriformis Glyceraldehyde‐3‐Phosphate Dehydrogenase

Abstract: Previous reports showed that hydrogen peroxide and the NO-generating reagent sodium nitroprusside (SNP)-modulated enzymatic activity of animal glyceraldehyde-3-phosphate dehydrogenase (GAPDH, EC 1.2.1.12). These modifications are suggested to have a physiological regulatory role. To gain further insight into this regulatory process the model ciliated protozoan Tetrahymena pyriformis was chosen. Both reagents inhibited growth of T. pyriformis cultures and produced a specific increase of GAPDH protein but only N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 45 publications
4
6
0
Order By: Relevance
“…5(B)]. These observations are in accordance with those reported by Fourrat et al [20] for the same enzyme from T. pyriformis, and suggest that GAPDH could be used to characterize the physiological effect of oxidative and nitrosative stress. Study in U937 cells (human promonocytes derived from a histiocytic lymphoma) has found that GAPDH is inactivated by the hydrogen peroxide, as a part of a cell defense pathway against oxidative stress induced apoptosis [6].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…5(B)]. These observations are in accordance with those reported by Fourrat et al [20] for the same enzyme from T. pyriformis, and suggest that GAPDH could be used to characterize the physiological effect of oxidative and nitrosative stress. Study in U937 cells (human promonocytes derived from a histiocytic lymphoma) has found that GAPDH is inactivated by the hydrogen peroxide, as a part of a cell defense pathway against oxidative stress induced apoptosis [6].…”
Section: Discussionsupporting
confidence: 82%
“…Effect of H 2 O 2 and SNP on the purified T. thermophila GAPDH In order to investigate the physiological effect of oxidative and nitrosative stress on T. thermophila, we selected GAPDH as H 2 O 2 and NO-sensitive enzyme, based on previous studies in animal cells, Tetrahymena pyriformis [20] and Saccharomyces cerevisiae [21]. The purified T. thermophila GAPDH was incubated at various concentrations of two agents of stress; H 2 O 2 and SNP a NO-donating compound.…”
Section: Effect Of Ph and Temperature On The Purified Gapdh Activitymentioning
confidence: 99%
“…In this study, the experimental perturbations in redox status were caused by the H 2 O 2 , it belongs to the group of reactive oxygen species (ROS). The action of this oxidant agent on T. pyriformis showed an increase in MDA level; this result is also observed by Fourat et al (2007) in T. pyriformis after oxidative and nitrosative stress. This increase of lipid peroxidation might be explained by the attack of radicals, such as ROS and reactive nitrogen species (RNS) to polyunsaturated fatty acid residues of phospholipids generating many aldehydes including the MDA (Nair et al, 2007).…”
Section: Discussionsupporting
confidence: 68%
“…sulfonation, nitrosylation, or glutathionylation; Bedhomme et al, 2012) were not the cause of the apparent inactivation. Interestingly, Fourrat et al (2007) showed that treatments of the protozoan Tetrahymena pyriformis with either sodium nitroprusside (NO donor) or H 2 O 2 led to a dramatic increase of GAPDH protein level without affecting total enzymatic activity.…”
Section: Cadmium Induces Accumulation Of No and Cytosolic Oxidation Imentioning
confidence: 99%